Wspieranie rozwoju i innowacyjności instytucji otoczenia biznesu przez samorząd gminny - Filipiak, Beata; Kogut-Jaworska, Magdalena (Support Given by Self-government in Order to Create and Develop Business Friendly Environment at Community Level (Based on Surveys Conducted in Zachodniopomorskie Region), 2008)
Local authorities should stimulate involvement of local communities in economic processes and positively influence economic activity of local enterprises. The article presents basic aspects related to local interventionism, in particular expenditures connected with creating a financial basis for business environment. It means financial support for local entrepreneurial funds and trusts, agencies for regional development, training centres, technological parks and crediting institutions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 35-44